Development of a wastewater treatment system for chromium removal using chitosan - Ahmed Kabashi, Nassereldeen; Hamid Nour, Abdurahman; Muyibi, Suleyman Aremu; Qudsieh, Isam Y. (Knowledge Review, Malaysia, 2009)
This study attempts to evaluate the removal of chromium from aqueous solution using chitosan as an adsorbent. The experiment was conducted by varying chitosan dosage (10-30 mg), pH (5-8), contact time (10-90 min) and agitation speed (50-250 rpm). The initial Cr concentration was fixed to 20 mg L-1. The results indicated that pH is the most significant factor that affects the removal of Cr. The R2 of 0.9963 showed that the overall model is good as the experimental values are close to predicted values. The optimized conditions obtained at 28.79 mg chitosan dosage, pH 6.40, 20.20 min contact time and agitation speed of 156.20 rpm. This optimum condition obtained to achieve 0.05 mg L-1 residual Cr concentration or 99.75% removal that meets Department of Environment Malaysia (DOE) effluent discharge requirement. The design of treatment system that consists of rapid mix, sedimentation and filtration unit is based on the optimum operating conditions. Rapid mix tank was designed with surface area of 9.18 m2 and volume of 27.8 m3. Sedimentation basin was designed with surface area of 100 m2 and volume of 83.33 m3. Filtration was designed with surface area of 16.67 m2.